KEMAMPUAN KOGNITIF PESERTA LATSAR CPNS DALAM PENCAPAIAN KINERJA PEGAWAI - Suharno Suharno (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2020)
This study aims to determine the effect of Cognitive Ability of CPNS Latsar participants on Employee Performance in the Sragen Regency Government. The object of this research is the CPNS Alumni Latsar 2019 as long as they carry out their duties during a probationary period at the agency where they work. This type of research is a survey research conducted on 66 employees. Sources of research data are employees (alumni of Latsar CPNS), the Organizing Committee, and employee superiors. Data were collected using interview techniques, observation, document study, and questionnaires. Data processing was carried out quantitatively and data analysis using simple linear regression using SPSS 17. The results of data analysis were discussed based on expert opinion and the results of previous studies were used to conclude the research results. Based on the results of the study it can be concluded that the Cognitive Ability of CPNS Participants has a very weak effect on employee performance, the value of the influence of Cognitive Ability on Employee Performance is 0.071. While the magnitude of the influence (R2) of Cognitive Ability on Employee Performance is 0.005; it means that Cognitive Ability affects Employee Performance only by 5%, while 95% is influenced by other factors not examined in this study. It is obtained that the number Constant (a) is 64.858 and the Number Y (b) is 1.279; so the regression equation is 64.858 + 1.279 X, meaning that if there is no cognitive ability value, the performance value is 64.858. With a regression coefficient of 1.279, it means that every addition of 1 cognitive ability value will add a performance value of 1.279. The implication of the results of this study is that efforts to sharpen learning in material that support the Strengthening of Technical Competence in the Field of Duty are needed, because this material is related to the job duties of employees.